The Association of the Childbirth Planning and Complication Prevention (P4K) Program with Reduced Risk of Delivery Complications in Ambon City - Susilowati, Virgin; Nukuhaly, Hasnawati (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2025)
This study investigates the effectiveness of the Childbirth Planning and Complication Prevention (P4K) program in reducing birth complications among postpartum women at 24 primary healthcare centers in Ambon City. A cross-sectional design was used with 200 respondents. Data were collected through structured questionnaires and analyzed using logistic regression. The findings revealed that most respondents had good access to ANC services (78.5%), planned their childbirth (78.1%), and were assisted by health professionals during delivery (78.5%). Complications occurred in 23.5% of cases. Significant correlations were found between complications and standardized ANC (p=0.031), childbirth planning (p=0.035), and skilled birth attendance (p=0.000), while sociodemographic factors showed no significant associations. Notably, mothers without standardized ANC or delivery planning had a 21 times higher risk of complications. Those not assisted by professionals had a 69 times higher risk. The study concludes that the P4K program is crucial in minimizing childbirth risks, emphasizing the importance of ANC, birth planning, and skilled attendance.